Sites forlorn: dating intervals of abandonment at three shell middens on Santa Cruz Island, California using Bayesian chronological models - Thakar, H. B. (Journal of Archaeological Science, 2014)
Archaeologists interested in variable mobility patterns and the factors that influence them rely on chronometric data to illuminate repetitive cycles of occupation, abandonment, and reoccupation. This article establishes and interrogates Bayesian chronological models in order to provide formal age estimates for two distinct intervals of site abandonment at three substantial multi-component shell middens from Santa Cruz Island, California. The earlier, more protracted interval of abandonment (ca. 2629–1698 cal. BP) following terminal Early Period occupation at each site location represents a temporal datum for a series of significant cultural, demographic, and technological developments throughout the region. I propose that this interval of localized site abandonments indicates a period of reorganization provoked by a shift in the paleoenvironment, a preliminary hypothesis that requires further testing. This research calls for development of similarly rigorous site chronologies on Santa Cruz Island and throughout the region that will shed further light on the validity of the temporal gaps documented in this analysis and most certainly will facilitate the development of additional hypotheses. More broadly, this article highlights the implementation and benefit of a Bayesian approach to building and interrogating site chronologies.
Au6tmTimes Cited:0Cited References Count:55